Quality of Life Among Chronic Liver Disease Patients: An Exploratory Cross Sectional Survey - Jyoti; Manisha Saklani; Jyoti Sarin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: QOL is the general well-being of individuals and societies, outlining negative and positivefeatures of life. It observes life satisfaction, including everything from physical health, family, education,employment, wealth, religious beliefs, finance and the environment.1 Quality of life has an important statusin patient management suffering from chronic liver disease.Objectives: The present study was done to assess the quality of life among patients suffering from ChronicLiver Diseases.Material and Methods: A descriptive explorative cross-sectional research design was used. Data wascollected from 165 patients using purposive sampling technique. The quality of life Scale (QOLS) was usedto assess the quality of life among chronic liver diseases patient admitted at Institute of Liver and BiliarySciences. MELD and CTP score was used to assess the mortality and survival rate among chronic liverdiseases patient. The study participants and their care givers were informed that the study is harmless; all thegathered data was treated confidentially and used for research purpose only.Results: The results of the study revealed that 0.6 percent of the patients have poor, in 35.2 percent of thepeople have moderate whereas 64.2 percent of the people have good quality of life. In terms of physicalwellbeing of patient 11.52 percent of the people have poor, 73.93 percent have moderate while only 14.55percent have good quality of life. In relation with social wellbeing of the patient 0.61 percent of the peoplehave poor, 27.88 percent have moderate while only 17.51 percent have good quality of life. As per emotionalwellbeing of the patient 3.03 percent of the people have poor, 87.88 percent have moderate while only 9.09percent have good quality of life. In terms of functional wellbeing of patient 3.03 percent of the peoplehave poor, 60 percent have moderate while only 36.97 percent have good quality of life. The quality of lifein terms of cost showed that 11.52 percent of the patient had poor, 73.93 percent had moderate, and 14.55percent of the patient has good quality of life. The quality of life in terms of limitation due to signs andsymptoms showed that 1.21 percent of the patient have poor, 81.82 percent have moderate whereas 16.97percent of the patient had good quality of life. The weak positive correlation (r=0.48) was found betweenMELD and CTP score.Conclusion: The study concluded that only 35.2 percent of the patient have moderate quality of life, morethan half (64.2%) of the patient have good quality of life. So, the effective steps need to be taken to improvethe quality of life among patients with Chronic Liver Diseases.